The Relationship Between Mother’s Knowledge About Balanced Nutrition And The Nutritional Status Of Under-Five Children In Bendo Village - Mirthasari Palupi; Riski Putri Arumsari (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: Nutritional status is a physical condition caused by intake and nutritional needs. Malnutrition can cause delayed physical and intellectual development, impacting morbidity and mortality, especially in children <5 years. This study examined the relationship between a mother's knowledge of balanced nutrition and the nutritional status of children under two in Bendo Village.Research Methods: The research design used is correlation analytic with a cross-sectional approach and uses Spearman Rank correlation at a significance level of 0.05. The target of this research is all mothers with children under five in Bendo Village. The sample used is 72 respondents and uses a simple random sampling technique. The data obtained is by giving ten questionnaire questions and observation sheets. Research Result: The results showed that mothers with good knowledge, according to the indicators of BB/U, had children with an average weight of 90.3% and a risk of weight greater than 9.7%. For mothers with good knowledge of the TB/U index, 93.1% of normal children and 6.9% of short children. Meanwhile, mothers with good knowledge, according to the indicators of BB/TB, have 75% of their children are good, 4.2% are malnourished, 16.7% are at risk of overnutrition, 1.4% are at risk of overnutrition, 1.4% are obese, 2.8%. Conclusion: The results of the Rank Spearman statistical test showed that there was no significant relationship between the mother's knowledge about balanced nutrition with indicators of BB/U (sig 0.506), TB/U (sig 0.580), and BB/TB (sig 0.772) because the value was > 0.05.